Charged vacancy induced enhanced piezoelectric response of reactive assistive IBSD grown AlN thin films. (22nd November 2016) - Sharma, Neha; Rath, Martando; Ilango, S; Ravindran, T R; Ramachandra Rao, M S; Dash, S; Tyagi, A K
Abstract: Piezoelectric response of AlN thin films was investigated in a AlN/Ti/Si(1 0 0) layer structure prepared by ion beam sputter deposition (IBSD) in reactive assistance of N + / N 2 + ions. The samples were characterized for their microstructure, piezoelectric response and charged defects using high resolution x-ray diffraction (HR-XRD), piezo force microscopy (PFM) and photoluminescence (PL) spectroscopy respectively. Our results show that the films are highly textured along the a -axis and charged native point defects are present in the microstructure. Phase images of these samples obtained from PFM show that the films are predominantly N-polar. The measured values of piezoelectric coefficient d 33(eff) for these samples are as high as 206 ± 20 pm V −1 and 668 ± 60 pm V −1 calculated by piezo response loop for AlN films of a thickness of 235 nm and 294 nm respectively. A mechanism for high d 33(eff) values is proposed with a suitable model based on the charged defects induced enhanced polarization in the dielectric continuum of AlN.